2007
DOI: 10.1073/pnas.0702254104
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates target multiple sites in both cis - and trans -prenyltransferases

Abstract: Bisphosphonate drugs (e.g., Fosamax and Zometa) are thought to act primarily by inhibiting farnesyl diphosphate synthase (FPPS), resulting in decreased prenylation of small GTPases. Here, we show that some bisphosphonates can also inhibit geranylgeranyl diphosphate synthase (GGPPS), as well as undecaprenyl diphosphate synthase (UPPS), a cis-prenyltransferase of interest as a target for antibacterial therapy. Our results on GGPPS (10 structures) show that there are three bisphosphonate-binding sites, consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
272
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 178 publications
(290 citation statements)
references
References 19 publications
12
272
0
6
Order By: Relevance
“…Moreover, the two sets of results are themselves quite close, with neither the extreme entropy or enthalpy driven behavior seen with FPPS (39), suggesting either that the charge center does not contribute to binding in GGPPS, or that the presence of the large neutral side chain simply reduces the effects of the cation center. The former view is supported by the observation in S. cerevisae GGPPS that the cation center is not essential for GGPPS inhibition (36), unlike the situation with FPPS (3).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, the two sets of results are themselves quite close, with neither the extreme entropy or enthalpy driven behavior seen with FPPS (39), suggesting either that the charge center does not contribute to binding in GGPPS, or that the presence of the large neutral side chain simply reduces the effects of the cation center. The former view is supported by the observation in S. cerevisae GGPPS that the cation center is not essential for GGPPS inhibition (36), unlike the situation with FPPS (3).…”
Section: Resultssupporting
confidence: 66%
“…As we and others reported previously (30,35,36), there are four main ligand (substrate or inhibitor) binding sites in human and S. cerevisae GGPPS, illustrated in (Fig. 3A).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The size of the cleft is strongly involved in the regulation of the final product chain length (9,11,12,26,(33)(34)(35)(36)(37)(38)(39). The crystal structure of GGPP synthase from Saccharomyces cerevisiae (Sc-GGPPs) with its final product GGPP revealed that the hydrophobic tail of the product just fits the cleft in both of the two homodimeric subunits (18). Many mutagenesis investigations at the interior of the hydrophobic cleft have reported that the deeper cleft synthesizes the longer final product (12).…”
mentioning
confidence: 99%
“…For instance, various bisphosphonate compounds mimicking diphosphate substrates have been found to inhibit UppS via a competition with C 15 -PP for enzyme binding. 36,127 Three dimensional structures of UppS-inhibitor complexes showed that several of these compounds occupied the enzyme active-site tunnel. High-throughput screening also provided several leads that were found to inhibit the growth of S. pneumoniae with satisfactory minimum inhibitory concentrations as a result of UppS activity inhibition.…”
Section: Synthesis Of Bacterial Undecaprenyl-diphosphatementioning
confidence: 99%